2020
DOI: 10.2196/14983
|View full text |Cite
|
Sign up to set email alerts
|

A Cardiology Handbook App to Improve Medical Education for Internal Medicine Residents: Development and Usability Study

Abstract: Background At most institutions, internal medicine residents struggle with balancing clinical duties and learning opportunities, particularly during busy cardiology ward rotations. To improve learning experiences for residents, we helped develop a cardiology handbook app to supplement cardiology education. Objective The aim of this study was to report the development, implementation, and preliminary impact of the Krannert Cardiology Handbook app on grad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Three articles presented mobile applications (apps), designed to be downloaded onto a handheld device and accessed on-the-go and one utilised mobile phones to deliver remote teaching and assessment ( Al-Jundi et al ., 2017 ; Torabi, Khemka and Bateman, 2020 ; Bhatheja et al ., 2018 ; Brewer et al ., 2016 ). Apps included a cardiology handbook and two surgical training skills apps, designed as supplemental teaching to improve learning experiences.…”
Section: Resultsmentioning
confidence: 99%
“…Three articles presented mobile applications (apps), designed to be downloaded onto a handheld device and accessed on-the-go and one utilised mobile phones to deliver remote teaching and assessment ( Al-Jundi et al ., 2017 ; Torabi, Khemka and Bateman, 2020 ; Bhatheja et al ., 2018 ; Brewer et al ., 2016 ). Apps included a cardiology handbook and two surgical training skills apps, designed as supplemental teaching to improve learning experiences.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous fields of education have widely used computer devices and mobile applications. Some studies have indicated the improvement of the learning experience through various forms of technology, such as digital handbook apps, mobile learning, computer device, and gamification [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The collaboration model could also improve the experience. Then, the available resources could lead to further curiosity [3]. The availability of good Internet access might be an issue in mobile learning.…”
Section: Introductionmentioning
confidence: 99%